2015
DOI: 10.1109/tasc.2014.2382877
|View full text |Cite
|
Sign up to set email alerts
|

Winding Configuration and Performance Investigations of a Tubular Superconducting Flux-Switching Linear Generator

Abstract: Primary permanent-magnet linear generators have an advantage of a simple secondary structure, which is suitable for the application of wave energy conversion. Based on vernier hybrid machines (VHMs), which are widely used for direct-drive wave energy converters, this paper proposes a tubular superconducting flux-switching linear generator (TSFSLG), which can effectively improve the performance of this kind of generators. Magnesium-diboride (MgB 2 )-type direct current superconducting windings are used in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…Zhang et al [88] changed the geometry parameters of the slot so that the effect of the Halbach PM array configuration on the electromagnetic properties of the generator and design guides were established for optimization of the key design parameters. There are also studies on how to avoid the irreversible demagnetization of magnets using the superconducting windings [57,89,90,91].…”
Section: Direct Drive and In-direct Drive Power Take-off Systemsmentioning
confidence: 99%
“…Zhang et al [88] changed the geometry parameters of the slot so that the effect of the Halbach PM array configuration on the electromagnetic properties of the generator and design guides were established for optimization of the key design parameters. There are also studies on how to avoid the irreversible demagnetization of magnets using the superconducting windings [57,89,90,91].…”
Section: Direct Drive and In-direct Drive Power Take-off Systemsmentioning
confidence: 99%
“…The power takeoff devices play a vital role in converting the irregular wave motion to a regular motion for energy conversion. Linear generators (LGs) have directly been implemented to the direct drive wave energy conversion without using medium devices which has unique advantages over all other wave energy devices [21]. An LG has two major parts, namely, translator and stator.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of permanent magnet linear generators (PMLGs) have been designed and analyzed for improved performance. The flat and tubular flux switching permanent magnet linear generators (FSPMLGs) have been proposed [21,24,25]. Different analyses have shown that the FSPMLGs made of PMs and steel cores have suffered from the problem of higher leakage flux leading to the reduction of electrical power generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, there are significant challenges for power grids to manage the stability, security and reliability while smoothing the generated power and thus make the best use of renewable energy sources [4]. At present, the major linear generators used for wave energy extraction are permanent magnet (PM) linear synchronous machines that usually have PMs on the translator [5], [6]. The traditional linear generators have the disadvantages of complex translator structure and unexpected translator temperature rise, which might cause irreversible demagnetization of magnets and mechanical damage [7].…”
Section: Introductionmentioning
confidence: 99%